Atrioventricular Optimized Direct His Bundle Pacing Improves Acute Hemodynamic Function in Patients With Heart Failure and PR Interval Prolongation Without Left Bundle Branch Block - Sohaib,SMA; Wright,I; Lim,E; Moore,P; Lim,PB; Koawing,M; Lefroy,DC; Lustgarten,D; Linton,NWF; Davies,DW; Peters,NS; Kanagaratnam,P; et al. (JACC: Clinical electrophysiology, 2015)
ObjectivesThe purpose of this study was to investigate whether heart failure patients with narrow QRS duration (or right bundle branch block) but with long PR interval gain acute hemodynamic benefit from atrioventricular (AV) optimization. We tested this with biventricular pacing and (to deliver pure AV shortening) direct His bundle pacing.BackgroundBenefits of pacing for heart failure have previously been indicated by acute hemodynamic studies and verified in outcome studies. A new target for pacing in heart failure may be PR interval prolongation, which is associated with 58% higher mortality regardless of QRS duration.MethodsWe enrolled 16 consecutive patients with systolic heart failure, PR interval prolongation (mean, 254 ± 62 ms) and narrow QRS duration (n = 13; mean QRS duration: 119 ± 17 ms) or right bundle branch block (n = 3; mean, QRS duration: 156 ± 18 ms). We successfully delivered temporary direct His bundle pacing in 14 patients and temporary biventricular pacing in 14 participants. We performed AV optimization using invasive systolic blood pressure obtaining parabolic responses (mean R2: 0.90 for His, and 0.85 for biventricular pacing).ResultsThe mean increment in systolic BP compared with intrinsic ventricular conduction was 4.1 mm Hg (95% confidence interval [CI]: +1.9 to +6.2 mm Hg for His and 4.3 mm Hg [95% CI: +2.0 to +6.5 mm Hg] for biventricular pacing. QRS duration lengthened with biventricular pacing (change = +22 ms [95% CI: +18 to +25 ms]) but not with His pacing (change = +0.5 ms [95% CI: −2.6 to +3.6 ms).ConclusionsAV-optimized pacing improves acute hemodynamic function in patients with heart failure and long PR interval without left bundle branch block. That it can be achieved by single-site His pacing shows that its mechanism is AV shortening. The improvement is ∼60% of the effect size previously reported for biventricular pacing in left bundle branch block. Randomized, blinded trials are warranted to tes